(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The main point is show the new reseracher in the field master degree studies in education, considering scientificity as an unknown field for this agent. For this, a bibliographical research was carried out based on the syllabus of the Master’s in Education course at the Federal University of Paraná, Research in Culture, School and Formative Processes in Education I in 2021. Through her, is addressed the scientificity placed to academic selectivity is addressed. In addition, the construction of the educational researcher’s identity is discussed, qualitative instrumentation is discussed and, finally, the teacher’s engagement, highlighted in educational research, is discussed.